Mesoscale connectivity of the human hippocampus and fimbria revealed by ex vivo diffusion MRI - Madeline McCrea; Navya Reddy; Kathryn Ghobrial; Ryan Ahearn; Ryan Krafty; T. Kevin Hitchens; Jorge Martinez-Gonzalez; Michel Modo (NeuroImage)
The human hippocampus is essential to cognition and emotional processing. Its function is defined by its connectivity. Although some pathways have been well-established, our knowledge about anterior-posterior connectivity and the distribution of fibers from major fiber bundles remains limited. Mesoscale (250 μm isotropic acquisition, upsampled to 125 μm) resolution MR images of the human temporal lobe afforded a detailed visualization of fiber tracts, including those that related anterior-posterior substructures defined as subregions (head, body, tail) and subfields (cornu ammonis 1–3, dentate gyrus) of the hippocampus. Fifty pathways were dissected between the head and body, highlighting an intricate mesh of connectivity between these two subregions. Along the body subregion, 12 lamellae were identified based on morphology and the presence of interlamellar fibers that appear to connect neighboring lamellae at the edge of the external limb of the granule cell layer (GCL). Translamellar fibers (i.e. longitudinal fibers crossing more than 2 lamellae) were also evident at the edge of the internal limb of the GCL. The dentate gyrus of the body was the main site of connectivity with the fimbria. Unique pathways were dissected within the fimbria that connected the body of the hippocampus with the amygdala and the temporal pole. A topographical segregation within the fimbria was determined by fibers’ hippocampal origin, illustrating the importance of mapping the spatial distribution of fibers. Elucidating the detailed structural connectivity of the hippocampus is crucial to develop better diagnostic markers of neurological and psychiatric conditions, as well as to devise novel surgical interventions.